Historical perspectives on the Aka and Baka Pygmies in the western Congo basin - (:unkn) unknown (My University, 1987)
Several ethnological descriptions of some Pygmy groups in central Africa are published; some works try to compare the Different groups, other try to understand the ecological basis of the life in forest, and to discover their roots and antiquity, but very few studies pay attention to the linguistic status of the various groups. The usual opinion is that Pygmies do speak the same language as the neighboring villagers . We found something very different, working firstly among the Aka during more than 12 years, and recently among the Baka. Each of these groups has his own language, each of them is easy to classify among the African languages, but fully isolated and recognizable. The question is then, how in the past, these groups borrowed their language? The second question is what kind of relationship exists between the various Pygmy groups in Africa, and particularly between Aka and Baka ? In this paper I will show how much rich are the informations on historical nature that give to us the lexical and semantical studies of the Pygmy languages.
Keywords: African Research